2021
DOI: 10.3390/diagnostics11122363
|View full text |Cite|
|
Sign up to set email alerts
|

SCORE2 Assessment in the Calculation of Cardiovascular Risk in Patients with Rheumatoid Arthritis

Abstract: Patients with rheumatoid arthritis (RA) are at increased risk for cardiovascular disease (CVD). Risk chart algorithms, such as the Systematic Coronary Risk Assessment (SCORE), often underestimate the risk of CVD in patients with RA. In this sense, the use of noninvasive tools, such as the carotid ultrasound, has made it possible to identify RA patients at high risk of CVD who had subclinical atherosclerosis disease and who had been included in the low or moderate CVD risk categories when the SCORE risk tables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…According to the re-evaluation (SCORE2 table) 34% of the respondents pertain to the high risk category, and 8% of the respondents pertain to the very high risk category. 26 As both studies showed significant differences between the percentages of subjects in certain categories, it is certainly necessary to emphasize the need to adapt to the latest guidelines and to change the existing therapy in the subjects in order to achieve the target values of LDL cholesterol. Due to estrogen deficiency, postmenopausal women are at an increased risk of developing cardiovascular diseases, which is certainly influenced by increased waist circumference, hypertension, hypertriglyceridemia, hyperglycemia, and reduced HDL cholesterol values, which are often present.…”
Section: Discussionmentioning
confidence: 98%
“…According to the re-evaluation (SCORE2 table) 34% of the respondents pertain to the high risk category, and 8% of the respondents pertain to the very high risk category. 26 As both studies showed significant differences between the percentages of subjects in certain categories, it is certainly necessary to emphasize the need to adapt to the latest guidelines and to change the existing therapy in the subjects in order to achieve the target values of LDL cholesterol. Due to estrogen deficiency, postmenopausal women are at an increased risk of developing cardiovascular diseases, which is certainly influenced by increased waist circumference, hypertension, hypertriglyceridemia, hyperglycemia, and reduced HDL cholesterol values, which are often present.…”
Section: Discussionmentioning
confidence: 98%
“…Because the prediction of major adverse CV events (MACE) is an unmet clinical need in RA management, numerous initiatives have been undertaken to optimize CV risk stratification in RA using various models combining clinical features, radiological, and/or biomarkers. Unfortunately, proposed models of cardiovascular risk predictions have only resulted in moderated discriminative capacity, with areas under the curve (AUC) in the range of 0.70-0.80, which is why further improvements are deemed necessary (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, well-known risk assessment tools such as the systematic coronary risk evaluation (SCORE) underestimate the actual risk of CVD in RA patients [10]. Thus, there is a significant need for developing optimal methods of assessment and analysis of CVD risk among RA patients.…”
Section: Introductionmentioning
confidence: 99%